2007
DOI: 10.1007/s10899-007-9073-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Reinforcement and Gaming Machine Choice

Abstract: Post-print of: Haw, J 2008, 'The relationship between reinforcement and gaming machine choice ' , Journal of Gambling Studies, vol. 24, no. 1,. The original publication is available at www.springerlink.com, http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
27
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 10 publications
8
27
1
Order By: Relevance
“…One possibility for this discrepancy is that the core dimensions measured by the GEQ do not capture the role of sound in slot machine games. In slot machine games there is no violence, no story and no skill, and it may be that slots games preferentially activate arousal via their variable ratio reinforcement schedules (Haw 2008). For this arousal dimension, players in this experiment indicated that sound played a key role.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility for this discrepancy is that the core dimensions measured by the GEQ do not capture the role of sound in slot machine games. In slot machine games there is no violence, no story and no skill, and it may be that slots games preferentially activate arousal via their variable ratio reinforcement schedules (Haw 2008). For this arousal dimension, players in this experiment indicated that sound played a key role.…”
Section: Discussionmentioning
confidence: 99%
“…Both laboratory studies and self-reports have examined the relationship between the reward characteristics of a game and gambling behaviors (e.g., Coates and Blaszczynski 2012 ; Dixon et al 2006 ; Haw 2007 ; Livingstone and Woolley 2008 ; McCormack and Griffiths 2013 ; Weatherly and Brandt 2004 ). Livingstone and Woolley ( 2008 ) examined the attractiveness of several gaming machine features based on a telephone survey of 180 Australian regular gamblers.…”
Section: Introductionmentioning
confidence: 99%
“…Although self-reports have shown a general preference for reward characteristics, experimental studies of the relationship between gambling behavior and reward characteristics has provided less conclusive results. Some studies have failed to support an association between gambling behavior and reward characteristics (Weatherly and Brandt 2004 ); others have found only partial support for a relationship (Haw 2007 ), whereas others have reported support for a relationship between gambling behavior and reward characteristics (e.g., Coates and Blaszczynski 2012 ; Dixon et al 2006 ). Dixon et al ( 2006 ) found that gamblers prefer games with more frequent but smaller wins to games with less frequent and big wins.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite their rewarding properties, urge following wins did not differ statistically from urge ratings following losses or near-misses. Since Candy Crush wins are periodic and unpredictable (likely occurring in a random ratio schedule similar to slot machines), it was expected that wins would be a powerful reinforcement of behaviour in this context (Ferster and Skinner 1957; Haw 2008). The absence of significantly greater urge ratings for wins compared to losses and near-misses warrants further investigation in order to reliably understand the reinforcing nature of wins in Candy Crush.…”
Section: Discussionmentioning
confidence: 99%